Fast Expansion of the Asian-Pacific Genotype of the Chikungunya Virus in Indonesia - Anggraeni, Yusnita Mirna; Garjito, Triwibowo Ambar; Prihatin, Mega Tyas; Handayani, Sri Wahyuni; Negari, Kusumaningtyas Sekar; Yanti, Ary Oktsari; Hidajat, Muhammad Choirul; Prastowo, Dhian; Satoto, Tri Baskoro Tunggul; Manguin, Sylvie; Gavotte, Laurent; Frutos, Roger (Frontiers in Cellular and Infection Microbiology, 2021)
Chikungunya is repeatedly affecting Indonesia through successive outbreaks. The Asian genotype has been present in Asia since the late 1950s while the ECSA-IOL (East/Central/South Africa - Indian Ocean Lineage) genotype invaded Asia in 2005. In order to determine the extension of the circulation of the chikungunya virus (CHIKV) in Indonesia, mosquitoes were collected in 28 different sites from 12 Indonesian provinces in 2016-2017. The E1 subunit of the CHIKV envelope gene was sequenced while mosquitoes were genotyped using the mitochondrial cox1 (cytochrome C oxidase subunit 1) gene to determine whether a specific population was involved in the vectoring of CHIKV. A total of 37 CHIKV samples were found in 28 Aedes aegypti, 8 Aedes albopictus and 1 Aedes butleri out of 15,362 samples collected and tested. These viruses, like all Indonesian CHIKV since 2000, belonged to a genotype we propose to call the Asian-Pacific genotype. It also comprises the Yap isolates and viruses having emerged in Polynesia, the Caribbean and South America. They differ from the CHIKV of the Asian genotype found earlier in Indonesia indicating a replacement. These results raise the question of the mechanisms behind this fast and massive replacement.